Analisis Jembatan Busur Pejalan Kaki Berdasarkan Variasi Letak Lantai Kendaraan - Ardiansyah, M. Syukri; Ismeddiyanto, Ismeddiyanto; Suryanita, Reni (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Sturdy bridge construction has always been synonymous with large and impractical structures. New innovations are needed to create a bridge system that is practical but also robust in terms of strength. For this reason, pedestrian arc bridges are analyzed with deck variations. The purpose of this study is to obtain the optimum bridge model, in which the ratio of weight of bridge structure deflection is small. Three types of bridges were considered in this study e.g deck arch, through arch and a half through arch by comparing the stresses that occur as well as the weight ratio and bridge deflection. The most optimum bridge is that produced the smallest efficiency ratio value. The results of the analysis obtained are A Half-Through Arch which has the best performance in distributing internal forces evenly. The Deck Arch weight is 1,125.52 tons, A Half-Through Arch weighs 1,007.14 tons and the Through Arch weighs 975.61 tons. The maximum deflection on the Deck Arch is 243.41 mm, A Half-Through Arch is 309.95 mm and the Through Arch is 260.19 mm. Then, the efficiency ratio of Deck Arch is 4.62, A Half-Through Arch is 3.25 and Through Arch is 3.75. So, it can be concluded the most optimum bridge is A Half-Through Arch with the smallest efficiency ratio value of 3.25. A Half-Through Arch are more efficient 13.34% than Through Arch and 29.73% more efficient than Deck Arch.Keywords : Analysis of Bridges, Arch Bridge, Steel Bridge, Bridge Loading, Deflection, SAP2000.